The Influence of Transformational Leadership on Employee Performance Through Intrinsic Motivation and Organizational Citizenship Behavior as Intervening Variables: Study at the High Religious Court of Jakarta Indonesia - Adi Prasetya Wardana; Anisah, Hastin Umi (HM Publisher, 2023)
Transformational leadership is also important in creating a positive and productive work culture. Transformational leaders are able to develop strong relationships with their team members, build trust, and motivate them to achieve their best. This study aimed to determine and analyze the effect of transformational leadership (X) as an independent variable on employee performance (X2) as the dependent variable with intrinsic motivation (Z1) and organizational citizenship behavior (OCB) (Z2) as a mediating variable at the Religious High Court of Jakarta Indonesia. This research method uses a questionnaire with 100 employees of the Jakarta Religious High Court as a total sample. Variable measurement using the Likert Scale technique with a weight scale from 1 to 5. To determine the correlation between variable X to variable Y through variables Z1 and Z2 using structural equation modeling (SEM) analysis techniques and processed with the SmartPLS 3.0 program. The results of the study concluded that transformational leadership had a positive and significant effect on intrinsic motivation. Transformational leadership has a positive and significant effect on OCB. Transformational leadership has a positive and significant effect on employee performance. Intrinsic motivation has a positive and significant effect on OCB. Intrinsic motivation has a positive and significant effect on employee performance. OCB has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on employee performance through intrinsic motivation. Transformational leadership has a positive and significant effect on employee performance through OCB. Intrinsic motivation has a positive and significant effect on employee performance through OCB.